Education On Kangaroo Care And Nesting Method On Mother's Skills To Care For Low Birth Weight (LBW) Babies - Retno Palupi (Universitas STRADA Indonesia, 2026)
LBW babies are at risk of experiencing health problems, so they require intensive care, including kangaroo care and nesting methods. This research aims to determine the effect of education on kangaroo care and nesting methods on mothers' skills in caring for LBW babies. This research is a pre-experimental study with a two group pre and post test design without control design. The population in this study were mothers with LBW who were treated. The sample size in this study was 30 people who were taken using the technique. total sampling. statistical test with the Wilcoxon test. The results of the research from 15 respondents, almost all respondents had skills regarding kangaroo care methods in the good category, namely 13 respondents (86.7%), and from 15 respondents almost all respondents had nesting method care skills in the good category, namely 12 respondents (80 % ).The results of bivariate analysis using the Wilcoxon test obtained a p value of 0.005<0.05, so HI was accepted, which means that there is an influence between education on kangaroo method care skills. Based on the results of the Wilcoxon statistical test, a p value of 0.014<0.05 was obtained, so HI Accepted means that there is an influence between education and nesting method care skills. It can be used as evaluation material to improve educational methods that are more interesting and it is hoped that it can increase mothers' knowledge and skills in carrying out LBW care.